Nutritional status is associated with permanent tooth eruption chronology - Juliana Arid; Mariana Cecília Vitiello; Raquel Assed Bezerra da Silva; Léa Assed Bezerra da Silva; Alexandra Mussolino de Queiroz; Erika Calvano Küchler; Paulo Nelson-Filho (Universidade Estadual de Campinas, 2017)
Either obesity and underweight are public health concerns that affect the development of children. Aim: The aim of this study was to evaluate whether the nutritional status affects permanent tooth eruption chronology in Brazilian children. Methods: A hundred sixty children were examined by a pediatric dentistry and at the clinical examination, the number of erupted permanent teeth was evaluated. The anthropometric measurements of the children were determined, and they were divided into groups: underweight, eutrophic, overweight and obese. The association between delayed tooth eruption and nutritional status groups was evaluated using chi-square test. The Shapiro-Wilk test was used to verify the normality of the data. To compare the mean number of delayed teeth according to nutritional status' groups Kruskal-Wallis test with multiple comparison by Dunn's test was performed. Results: Fifty-six children had delayed tooth eruption in at least one permanent teeth and delayed tooth eruption was more common in underweight children than in eutrophic children (p=0.0091). Conclusion: In conclusion, our study suggests that underweight Brazilian children have a higher incidence of delayed eruption.